Actor networks in specialized accounting inspection: an analysis in the light of the Actor-Network Theory - Murro, Eduardo Vinícius Bassi (2016)
Purpose – This study investigated the configuration of human andnon-human actor networks that are formed in the process of specializedaccounting inspection from the Actor-Network Theory perspective.Design/methodology/approach – The population of the surveycomprised 593 accounting experts registered in Expert Associationsfrom the Brazilian states of Minas Gerais, Paraná, Rio de Janeiro, RioGrande do Sul and São Paulo, and the sample is made up of 102 validquestionnaires. Five judges and five accounting experts from Curitiba(state of Paraná) were also interviewed. Through Structural EquationModeling, the translation process indicated statistical significance,except in the relationship between human accounting actors, nonhumanactors and problematization.Findings – Based on this research, we concluded that the establishmentof networks in the field of specialized accounting inspection dependson numerous translations between agents, since they have an impact onthe performance of activities and the stabilization of relationships. Thequality of the expert report and technical report and the competenceof accounting experts were pointed out as performance indicators.Accounting experts and accounting experts assistant’s experience, theperiod of experience and the relationship with judges were identifiedas drivers of stable and lasting relationships between specializedaccounting inspection actors.Originality/value – The study is relevant given the lack of researchinvolving the Actor-Network Theory and accounting, particularlyAccounting Inspection, both nationally and internationally. Therefore,contribute to investigate how the actors interact, create and modifyrelationships, through the perception of accountants and judges.